Impact of Green Awareness, Green Brand Image, and Green E-WOM with Trust as a Mediation on the Intention to Buy Eco-Friendly Houses - Imaningsih, Erna Sofriana; Ramli, Yanto; Anggraeni, Adilla (Journal of Sustainable Economic and Business, 2024)
Being a green consumer is an essential contribution to addressing the environmental crisis. That is why making individual habits to embrace greener choices is crucial. Although the intention to purchase green products is increasing nowadays, the eco-friendly housing market still struggles. It is important to leverage green awareness, green brand images, and green electronic word of mouth (E-WOM) to promote a positive attitude toward the environment. However, consumer doubts regarding environmental issues can act as a barrier to increasing green intentions. This study aims to investigate how trust in green claims can mediate the relationships between green awareness, green images, and green E-WOM with the intention to buy eco-friendly houses. The hypotheses of the research are as follows: Green Trust mediates the relationship between green awareness and the intention to buy eco-friendly houses (H1); Green Trust mediates the relationship between green brand images and the intention to buy eco-friendly houses (H2); Green Trust mediates the relationship between green E-WOM and the intention to buy eco-friendly houses (H3). This research adopts a quantitative approach and utilizes a purposive sampling technique. The data collection method employed is an online questionnaire, administered to 100 consumers. Data processing is conducted using SmartPLS 4.0.